2021
DOI: 10.1111/ijcp.14037
|View full text |Cite
|
Sign up to set email alerts
|

Interventions supporting cost conversations between patients and clinicians: A systematic review

Abstract: Discussing costs during the medical encounter can help address patients' and physician's concerns about the costs and affordability for care. A recent national survey in the United States found that four out of 10 patients reported that it is somewhat or very difficult to afford health care. [1][2][3][4][5] Patient's financial hardship negatively affects the quality of life and their health outcomes. 4 Patients unable to afford health care may not have access to evidence-based treatment or might decide to post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In addition, more attention should be given to developing evidence-based interventions to support cost conversations, given that very few have been tested. 33 Finally, we found that the occurrence of cost conversations was associated with patients who reported that cost was an important factor in their selection of anticoagulant. However, the actual choice of medication was not significantly correlated with the incidence of cost conversations, suggesting that either these conversations were not productive or consequential, or that considerations other than drug costs (eg, satisfaction with the existing regiment or the need to avoid diet restrictions or periodic monitoring) were more important in selecting an anticoagulation agent.…”
Section: Jama Network Open | Cardiologymentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, more attention should be given to developing evidence-based interventions to support cost conversations, given that very few have been tested. 33 Finally, we found that the occurrence of cost conversations was associated with patients who reported that cost was an important factor in their selection of anticoagulant. However, the actual choice of medication was not significantly correlated with the incidence of cost conversations, suggesting that either these conversations were not productive or consequential, or that considerations other than drug costs (eg, satisfaction with the existing regiment or the need to avoid diet restrictions or periodic monitoring) were more important in selecting an anticoagulation agent.…”
Section: Jama Network Open | Cardiologymentioning
confidence: 83%
“…This hypothesis should be explored further. In addition, more attention should be given to developing evidence-based interventions to support cost conversations, given that very few have been tested …”
Section: Discussionmentioning
confidence: 99%
“…In 2009 the American Society of Clinical Oncology endorsed cost communication between patients and providers [9]. Despite this, patient preferences and values have mainly centered on the clinical experience of care (e.g., side effects, comorbidities of treatment); to date, the costs of care and their implications have not been widely included in shared cancer treatment decisions [38,39]. In a survey of over 600 women with breast cancer, Greenup et al found that 78% never discussed costs with their cancer team [23].…”
Section: Patient Cost Preferences and Values In Cancer Carementioning
confidence: 99%
“…15 Yet clinician communication and patient decision aids rarely include costs of treatment options to support decisions. 16 Although financial toxicity affects patients with cancer worldwide, [1][2][3][4][5] it is particularly a problem for patients in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Patients want to know about cost information 13,14 and clinicians acknowledge its importance and impact on patients' choices and adherence to care 15 . Yet clinician communication and patient decision aids rarely include costs of treatment options to support decisions 16 …”
Section: Introductionmentioning
confidence: 99%